2016
DOI: 10.29063/ajrh2016/v20i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Study of the Shang Ring Device for Adult Medical Male Circumcision in a Routine Clinical Setting in Malawi

Abstract: We evaluated the safety and acceptability of the ShangRing device for male circumcision during routine clinical service delivery in Namitete, Malawi. We conducted a prospective observational study enrolling 500 HIV-negative men ages 18 to 49 years at St. Gabriel's Hospital. Participants returned for two follow-up visits: the removal visit (day 7 after placement) and the healing check visit (day 42 after placement). We assessed pain, adverse events (AEs), acceptability, and healing. 500 men were screened; 498 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Our results demonstrate that the no-flip ShangRing technique, whether with device removal at 7 days after circumcision or allowing it to fall off, is safe, effective, and acceptable to clients 10 years and older. Circumcision and device removal times, AE rates, time to clinical wound healing, and participant satisfaction with the no-flip technique appear similar to historical data from Africa with the original flip technique 171819202136. Data from these studies show AE rates of 1.0%–7.5%, circumcision times of 5–7 min, and removal times of 2–5 min; consistent with our results for the no-flip technique.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results demonstrate that the no-flip ShangRing technique, whether with device removal at 7 days after circumcision or allowing it to fall off, is safe, effective, and acceptable to clients 10 years and older. Circumcision and device removal times, AE rates, time to clinical wound healing, and participant satisfaction with the no-flip technique appear similar to historical data from Africa with the original flip technique 171819202136. Data from these studies show AE rates of 1.0%–7.5%, circumcision times of 5–7 min, and removal times of 2–5 min; consistent with our results for the no-flip technique.…”
Section: Discussionsupporting
confidence: 88%
“…All were moderate, occurred during follow-up, were considered definitely related to the circumcision, and resolved with conservative management and without sequelae. Among participants with the no-flip technique and removal at 7 days, 5.3% (6/114; 95% CI: 1.2%–9.4%) had an AE, which was not higher, using a one-sided test, than the 3% from historical data with the flip technique ( P = 0.07) 17181920213637. Following circumcision with the no-flip technique and spontaneous detachment, 1.7% (2/116; 95% CI: 0–4.1%) of participants had an AE, also not different from previously published studies ( P = 0.79).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Much progress has been made over the past 10 years since that original article was published in Asian Journal of Andrology in 2008. In studies conducted in Kenya, Malawi, Uganda, and Zambia, the ShangRing has been shown to be safe, effective, and well-accepted by men and boys and by providers of adult and adolescent VMMC services 67891011. The device received a CE mark in 2008, FDA 510(k) clearance in 2012, and the WHO prequalification in 2015.…”
mentioning
confidence: 99%